2007
DOI: 10.1159/000111459
|View full text |Cite
|
Sign up to set email alerts
|

Photoperiod-Independent Hypothalamic Regulation of Luteinizing Hormone Secretion in a Free-Living Sonoran Desert Bird, the Rufous-Winged Sparrow <i>(Aimophila carpalis)</i>

Abstract: We investigated the regulation of luteinizing hormone (LH) in the male Rufous-winged Sparrow,Aimophila carpalis, a resident of the Sonoran desert that breeds after irregular summer rains. Although the testes develop in March due to increasing photoperiod and regress in September due to decreasing photoperiod, LH does not consistently increase in the spring as in other photoperiodic birds. However, throughout the year increased plasma LH is correlated with rainfall. To investigate this rainfall-associated regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 160 publications
(145 reference statements)
2
52
1
1
Order By: Relevance
“…As the development of the male reproductive system precedes that of the female, it is less likely that males will show an adaptive response to phenological cues to fine-tune gonadal development. Yet, in an opportunistic breeder, the rufous-winged sparrow (Aimophila carpalis), environmental factors associated with summer rains stimulated both gonadotropinreleasing hormone (GnRH) synthesis and LH secretion in males, which was, however, unrelated to gonadal growth earlier in the season ( Small et al, 2008). Similarly, the higher LH concentrations reported by Visser and colleagues did not induce a greater increase in testis size (Visser et al, 2002); also, in the present experiment there was only a weak correlation between female LH concentrations and actual laying date.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the development of the male reproductive system precedes that of the female, it is less likely that males will show an adaptive response to phenological cues to fine-tune gonadal development. Yet, in an opportunistic breeder, the rufous-winged sparrow (Aimophila carpalis), environmental factors associated with summer rains stimulated both gonadotropinreleasing hormone (GnRH) synthesis and LH secretion in males, which was, however, unrelated to gonadal growth earlier in the season ( Small et al, 2008). Similarly, the higher LH concentrations reported by Visser and colleagues did not induce a greater increase in testis size (Visser et al, 2002); also, in the present experiment there was only a weak correlation between female LH concentrations and actual laying date.…”
Section: Discussionmentioning
confidence: 99%
“…In non-equatorial birds, lengthening photoperiod in spring provides the principal cue for the timing of seasonal breeding (Dawson et al, 2001;Farner, 1985;Follett et al, 1985;Sharp, 2005;Silverin et al, 1993), but supplementary cues derived from rainfall, ambient temperature and phenology are available to increase the precision of a timing decision (Dawson, 2008;Hau et al, 2004;Perfito et al, 2005;Salvante et al, 2007;Schaper et al, 2011;Small et al, 2008;Visser et al, 2009;Wingfield et al, 1992) (but see Visser et al, 2011). The aims of this study were, firstly, to re-evaluate evidence for the involvement of phenological cues in the onset of egg laying in opportunistic and strictly seasonally breeding birds, and, secondly, to assess experimentally whether there is a causal relationship between phenological cues provided by leafing birch and caterpillars and the onset of reproduction in a seasonal breeder, the great tit (Parus major L.).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to testicular size, cloacal protuberance growth in finches was not affected by food availability. Cloacal protuberance size usually varies in parallel with testis size (Perfito et al, 2005;Small et al, 2008) and both are influenced by circulating testosterone levels (Deviche and Cortez, 2005). Although food-restricted finches had lower plasma testosterone than ad libitum-fed finches, it appears that the precise relationship between plasma testosterone and cloacal protuberance growth is somewhat dissociated, an observation that is not without precedent (Wingfield et al, 2012).…”
Section: Testicular Response To Energetic Deficitmentioning
confidence: 99%
“…Between two and four assays were performed for each neuropeptide, with birds from each treatment group equally represented on each assay. Immunocytochemical labeling was done using a previously published procedure (Deviche et al, 2000;Small et al, 2008). Briefly, free-floating sections were washed three times for 20 min in 0.1 mol l −1 PB, incubated in 0.36% hydrogen peroxide, washed 3 times for 5 min in 0.1 mol l −1 PB, incubated for 1 h in normal blocking serum, and incubated overnight at 4°C in primary antibody.…”
Section: Gnrh Prognrh Gnih and Npy Immunocytochemistrymentioning
confidence: 99%
“…For example, it has been shown that LH levels in male songbirds, even though primarily regulated by photoperiod, increase in response to environmental stimuli, such as the onset of rain [35], or the presence of leafing birch branches [44], but see [28]. Furthermore, if LH plasma concentrations are only loosely regulating gonadal development, the question remains which external or internal information is reflected in elevated LH concentrations, and which mechanisms might be affected further downstream.…”
Section: Approaches To Variation In Pre-laying Reproductive Endocrinomentioning
confidence: 99%